Long Noncoding RNAs in Neurodegenerative Diseases: Pathogenesis and Potential Implications as Clinical Biomarkers - Zhang, Meng; He, Ping; Bian, Zhigang (Frontiers in Molecular Neuroscience, 2021)
Neurodegenerative diseases (NDDs) including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD) and amyotrophic lateral sclerosis (ALS) are developmentally progressive fatal diseases. NDD onset can be influenced by several factors including heredity and environmental cues. Long noncoding RNAs (lncRNAs) are a class of noncoding RNA (ncRNA) molecules, and are characterized by i) lengths greater than 200 nucleotides (nt), ii) rich biological functions, and iii) highly conserved structures. They directly interact with molecules such as proteins and microRNAs (miRNAs) to regulate expression of these targets at genetic, transcriptional and post-transcriptional levels. Emerging studies have shown that lncRNAs play important roles in the progression of neurological diseases, including NDDs. Additionally, with improvements in detection technologies, it is possible to quantitatively detect and apply lncRNAs to circulating fluids in clinical settings. Here, we review the current state of the art of lncRNAs in animal models and patients with NDDs. We also discuss the potential applicability of circulating lncRNAs as biomarkers in NDD diagnostics and prognostics. In the future, a better understanding of the role of lncRNAs in NDDs is essential if we are to exploit these new therapeutic targets and improve non-invasive disease diagnostic methods.